THE SIGNIFICANCE OF TEACHING METHODS IN EDUCATION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article is based on giving essential information about methods of teaching foreign languages and its importance in the education system. Each subject has its own teaching way and psychology. In this article, modern psychological methods, approaches and instructions for teaching foreign languages are mentioned. Basic information about the essence of scientific research on foreign language learning and the psychological aspects of increasing the effectiveness of foreign language learning is presented.